Protocol of somatic embryo towards in vitro artificial inoculation on Aquilaria malaccensis Lamk. (gaharu) / Nordiana Najwa Ibrahim - Ibrahim, Nordiana Najwa (2016)
Aquilaria malaccensis Lamk. belongs to the Thymelaeaceae family and known as agarwood in the world and Gaharu in Malaysia, that is commercially identified as a potential aromatic plant. Inoculation for resinous compounds in A. malaccensis naturally is difficult. Hence, an artificial inoculation via in vitro inoculation method was developed. Stem explants of A. malaccensis were cultured on MS media supplemented with 1.0 mg/L BAP and 0.1 mg/L 2,4-D for the callus induction. Embryogenic callus was successfully initiated on MS media supplemented with 1.0 mg/L and 0.1 mg/L 2,4-D added with 500 mg/L casein hydrolysate by producing globular, heart-shaped and torpedo stages. Addition of additive including casein hydrolysate added with 10.0 mg/L absicic acid (ABA) give a significance effect on the development and maturation of the embryogenic callus. Therefore, induction of a high frequency of somatic embryogenesis in stem explants on MS media is possible. Optimum callus formation from MS media added with 500 mg/L casein hydrolysate and 10.0 mg/L ABA which was used to induce resin of A. malaccensis through in vitro artificial inoculation. The inoculant known as 4 Moon Booster which was inoculated into MS media then the interaction of the inoculant to embryogenic callus and media was successfully obtained. The result revealed that, embryogenic callus turned into dark brown from creamy white color and give an odour. In addition, the inoculated media were also turned to brown and produced a sense of sensory when the container cap is opened. So, the inoculant gives significance artificial inoculation effect on the embryogenic callus and to the media. A reliable protocol useful for A. malaccensis through somatic embryogenesis was successfully established for artificial inoculation purposes.